Letter from Max Bredig to Ludwig Bendix, March 15, 1941 - Bredig, Max Albert (1941)
Max Bredig (1902-1977) informs Ludwig Bendix (1877-1954), a New York investment banker, that he need not forward his recent letters to the American Consulate of Marseille. Bendix is a longtime friend and colleague of Viktor Homburger (1888-1968), Bredig's brother-in-law. Bendix is assisting Bredig in securing immigration visas for Viktor and his wife, Max's sister, Marianne Homburger (1903-1986).
Keywords: Bendix, Ludwig, 1877-1954; Bredig, Max Albert, 1902-1977; Emigration and immigration; Homburger, Marianne, 1903-1986; Homburger, Viktor, 1888-1968